La critica fenomenologica e i disturbi del Sé: implicazioni per la ricerca sugli Ultra-High Risk (“prodromi”)* - Nelson, Barnaby; Yung, Alison R.; Bechdolf, Andreas; McGorry, Patrick D.; Brandizzi, Martina; Masillo, Alice; Lo Cascio, Nella (Il sogno della farfalla, 2016)
Recent years have witnessed widespread interest in the early phase of schizophrenia and other psychotic disorders. Strategies have been introduced to attempt to identify individuals in the prepsychotic or prodromal phase. The most widely used of these approaches is the Ultra-High Risk (UHR) approach, which combines known trait and state risk factors for psychotic disorder. However, researchers guided by phenomenological theory have argued that modern psychiatry’s neglect of subjective experience has compromised researchers’ understanding of psychotic disorder and has thereby limited efforts at prospective and early identification. Phenomenological research indicates that disturbance of the basic sense of self may be a core marker of psychotic vulnerability, particularly of schizophrenia spectrum disorders. It is argued that identifying self-disturbance in the UHR population may provide a means of further ‘‘closing in’’ on individuals truly at high risk of psychotic disorder, thus supplementing the UHR identification approach. This would be of practical value in the sense of reducing inclusion of ‘‘false-positive’’ cases in UHR samples and of theoretical value in the sense of shedding light on core features of psychotic pathology. The strong explanatory power and empirical findings to date invite further research into the role of self-disturbance as a phenotypic vulnerability marker for psychotic disorder.